2017
DOI: 10.21767/2248-9215.100039
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Endometrioma; Outcome of Medical Management with Dienogest

Abstract: Background: Management of recurrent endometrioma should balance between the risk of unexpected hidden malignancy and the damaging effect of second surgery to ovarian tissue. Dienogest is a fourth generation of progestin and has been used in endometriosis with effective and save reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Aizzi reported a reduction of mean diameter of endometrioma from 5.45 cm baseline to 3.1 cm in twenty women treated with dienogest for 3 months. 23 By the end of the 6 th month's treatment, only 2 patients had residual cysts. Park et al 1 showed that by treatment with dienogest the size of endometrioma was significantly reduced at 12 months (30.9 versus 20.8 mm) and 18 months (20.5 versus 14.7mm).…”
Section: Discussionmentioning
confidence: 97%
“…Aizzi reported a reduction of mean diameter of endometrioma from 5.45 cm baseline to 3.1 cm in twenty women treated with dienogest for 3 months. 23 By the end of the 6 th month's treatment, only 2 patients had residual cysts. Park et al 1 showed that by treatment with dienogest the size of endometrioma was significantly reduced at 12 months (30.9 versus 20.8 mm) and 18 months (20.5 versus 14.7mm).…”
Section: Discussionmentioning
confidence: 97%